Development of EORTC/CLTF questionnaire to assess HRQOL in primary cutaneous T-cell and B-cell lymphomas: phase I. (October 2021) - Molloy, Kevin; Oerlemans, Simone; Jonak, Constanze; Porkert, Stefanie; Wehkamp, Ulrike; Guenova, Emmanuella; Fassnacht, Christina; Cozzio, Antonio; Zeller, Tanja; Quaglino, Pietro; Scarisbrick, Julia
Abstract : Background: Health-related quality of life (HRQoL) in patients with cutaneous lymphoma (CL) is negatively impacted by a large burden of disease symptoms including intractable itch, pain, discomfort and socially stigmatising cosmetic disfigurement which may adversely affect patient self-esteem and interpersonal relationships. There is currently no cure for CL and as such, accurate determination of patient HRQoL is of paramount importance. To date, the impact of both skin disease and of a cancer diagnosis on patient HRQoL in CL is assessed using separate, non-CL-specific questionnaires. A composite HRQoL questionnaire addressing all aspects of the disease is lacking. Methods: The EORTC Quality of Life Group questionnaire development guidelines were followed. For phase I, semi-structured interviews were conducted in 15 patients with early-stage mycosis fungoides (IA–IIA), 30 patients with late-stage mycosis fungoides/Sézary syndrome (IIB–IVB) (15 patients <3 years and >3 years from diagnosis) and 15 patients with cutaneous B cell lymphoma. Collaborators communicated during the patient recruitment to ensure balanced patient selection with respect to age, gender, stage, duration of the disease, and number of (previous) treatments. Results: Patients were recruited in 5 countries (6 centres) across Europe. So far, 62 patients participated (target 60) from each of the following representative patient groups: early MF (stage IA–IIA), late MF (stage IIB–IVB) and cutaneous B cell lymphoma. Data from patient interviews and questionnaires is being analyzed using basic quantitative analyses, including generation of descriptive statistics (e.g., %missing data, means and standard deviations, floor and ceiling effects, etc.), prevalence (number of patients who experienced each complaint i.e. who scored 2, 3 or 4, divided by the total number of patients who completed that item, multiplied by 100), priority ratings (number of patients and professionals who have given priority ratings to each item) and range of responses for each item. The data from the debriefing questions will be reported both quantitatively and qualitatively (in narrative form). Conclusion: Once completed, phase I issues will be operationalised into items and any new items created in a style and format compatible with the EORTC quality of life group translation guidelines (phase II). The preliminary module will be pre-tested in phase III followed by large-scale international field-testing in phase IV. A comprehensive HRQoL questionnaire (module) for patients with CL is being developed to more accurately measure assessment of the impact of HRQoL in patients with skin lymphomas.